(untitled) (Research, Society and Development, 2022)
Maternal mortality refers to any death that occurs during pregnancy or within 42 days of termination, regardless of location or duration, from any direct or indirect cause associated with a worsening pregnancy. The identification of the causes of maternal mortality has stimulated the investigation of the epidemiological profile of maternal mortality and the avoidable causes to improve the quality of care for women of childbearing age. Thus, the present study aims to provide information on the causes of direct and indirect maternal mortality, through an analysis of the profile of deaths, where the number of pregnancies that occurred between 2010 and 2020 in the state of Paraná was researched, relating them directly to the number of maternal deaths. This is an ecological study, which compares social and health indicators of the population, in the state of Paraná, the way of grouping the variables obeyed the availability of information in the system, through pre-fixed inclusion and exclusion criteria. As a result, it was found that the maternal mortality rate in Paraná is high. This study also showed the main factors associated with mortality, taking into account the causes and quality of care provided, highlighting the need for governments to invest in the training and qualification of professionals to assist women of reproductive age, prenatal care, childbirth, abortion and puerperium.